Intestinal inhibition of the Na+/H+ exchanger 3 prevents cardiorenal damage in rats and inhibits Na+ uptake in humans - Spencer, Andrew G; Labonte, Eric D; Rosenbaum, David P; Plato, Craig F; Carreras, Christopher W; Leadbetter, Michael R; Kozuka, Kenji; Kohler, Jill; Koo-McCoy, Samantha; He, Limin; Bell, Noah; Tabora, Jocelyn; et al. (Science translational medicine, 2014)
The management of sodium intake is clinically important in many disease states including heart failure, kidney disease, and hypertension. Tenapanor is an inhibitor of the sodium-proton (Na(+)/H(+)) exchanger NHE3, which plays a prominent role in sodium handling in the gastrointestinal tract and kidney. When administered orally to rats, tenapanor acted exclusively in the gastrointestinal tract to inhibit sodium uptake. We showed that the systemic availability of tenapanor was negligible through plasma pharmacokinetic studies, as well as autoradiography and mass balance studies performed with (14)C-tenapanor. In humans, tenapanor reduced urinary sodium excretion by 20 to 50 mmol/day and led to an increase of similar magnitude in stool sodium. In salt-fed nephrectomized rats exhibiting hypervolemia, cardiac hypertrophy, and arterial stiffening, tenapanor reduced extracellular fluid volume, left ventricular hypertrophy, albuminuria, and blood pressure in a dose-dependent fashion. We observed these effects whether tenapanor was administered prophylactically or after disease was established. In addition, the combination of tenapanor and the blood pressure medication enalapril improved cardiac diastolic dysfunction and arterial pulse wave velocity relative to enalapril monotherapy in this animal model. Tenapanor prevented increases in glomerular area and urinary KIM-1, a marker of renal injury. The results suggest that therapeutic alteration of sodium transport in the gastrointestinal tract instead of the kidney--the target of current drugs--could lead to improved sodium management in renal disease.